Extraction/export of nutrients in Opuntia ficus-indica under different spacings and chemical fertilizers - João A. da Silva; Sérgio L. R. Donato; Paulo E. R. Donato; Evilasio dos S. Souza; Milton C. Padilha Júnior; Ancilon A. e Silva Junior (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This work aimed to evaluate extraction/ export of nutrients and dry matter production in the 'Gigante' cactus pear, grown in different spacings and fertilizations 620 days after planting. Twelve combination of treatments were used consisting of: three spacings - 1.00 x 0.50; 2.00 x 0.25; and 3.00 x 1.00 x 0.25 m, and four fertilizations - 000-000-000; 000-150-000; 200-150-000; and 200-150-100, kg ha-1, of N, P2O5 and K2O, in a 3 x 4 factorial scheme in a randomized block design, with three replicates. Extraction/export of N, P, K, S, Ca, Mg, B, Fe, Mn, Zn, Na and Cu were determined and the means were 304.35; 18.81; 421.04; 62.35; 464.63; 215.77; 0.39; 0.81; 23.74; 1.11; 0.62 and 0.08 kg ha-1, besides the mean dry matter production of 17.11 Mg ha-1. There were significant interactions for extraction/export of Mg and dry matter production. The fertilizations used were insufficient to meet the demand of N, K, Ca, Mg, S and micronutrients. Fertilization increased the extraction of nutrients, particularly N, P and S at the spacing of 1.00 x 0.50 m, and increased dry matter production. The decreasing order of extraction/export was Ca, K, N, Mg, S and P for macronutrients and Mn, Zn, Fe, Na, B and Cu for micronutrients.